2018
DOI: 10.1021/acs.bioconjchem.8b00177
|View full text |Cite|
|
Sign up to set email alerts
|

A Trimethoprim Conjugate of Thiomaltose Has Enhanced Antibacterial Efficacy In Vivo

Abstract: Trimethoprim is one of the most widely used antibiotics in the world. However, its efficacy is frequently limited by its poor water solubility and dose limiting toxicity. Prodrug strategies based on conjugation of oligosaccharides to trimethoprim have great potential for increasing the solubility of trimethoprim and lowering its toxicity, but they have been challenging to develop due to the sensitivity of trimethoprim to chemical modifications, and the rapid degradation of oligosaccharides in serum. In this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 42 publications
2
20
0
1
Order By: Relevance
“…In parallel, data obtained from electrophysiology studies were consistent with these conclusions wherein Cpd-1 penetrates through reconstituted LamB channels better than Cpd-2. These general results wherein shorter saccharides provide improved accumulation are in agreement with recent results suggesting that a thiomaltose–perylene conjugate has better accumulation relative to a maltohexaose–perylene conjugate (26).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In parallel, data obtained from electrophysiology studies were consistent with these conclusions wherein Cpd-1 penetrates through reconstituted LamB channels better than Cpd-2. These general results wherein shorter saccharides provide improved accumulation are in agreement with recent results suggesting that a thiomaltose–perylene conjugate has better accumulation relative to a maltohexaose–perylene conjugate (26).…”
Section: Discussionsupporting
confidence: 91%
“…Several approaches have been explored to bypass these barriers including new adjuvants (permeabilizer, efflux pump inhibitors) to rejuvenate the antibacterial efficacy, Trojan horse strategies to hijack active transport pathways and provide efficient penetration, etc. However, crucial points with these strategies concern the internal biological activity and the precise localization of the molecule, and these aspects are generally not studied or reported in depth (25, 26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, agent‐based simulations revealed that the rate of prodrug activation (i.e., catalytic efficiency, k cat / K M ) had a strong effect on the MIC of each compound (Murphy et al , 2011 ). Furthermore, empirical studies have found there to be differences in MIC between parent and prodrug forms, as well as higher variance in prodrug MIC across bacterial strains, relative to the parent drug (Wang et al , 2018 ; Evans et al , 2019 ; Yang et al , 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…We design the linker substrate to be cleaved by E. coli protease OmpT, such that increasing concentrations of bacteria activate higher concentrations of free AMP. The trimethoprim prodrug comprises thiomaltose conjugated to trimethoprim via a self‐immolative disulfide linker, which releases TMP‐OH upon cleavage by free thiols inside bacterial cells without affecting the toxicity of the drug (Wang et al , 2018 ). Free TMP‐OH then kills bacteria by inhibiting tetrahydrofolic acid synthesis, which is a necessary cofactor for thymidine, purine, and bacterial DNA synthesis (Masters et al , 2003 ).…”
Section: Introductionmentioning
confidence: 99%